Breastfeeding in England: time trends 2005-2006 to 2012-2013 and inequalities by area profile. - Oakley, L; Kurinczuk, J; Renfrew, M; Quigley, M (2014)
Breastfeeding rates in England have risen steadily since the 1970s, but rates remain low and little is known about area-based trends. We report an ecological analysis of time trends in area breastfeeding rates in England using annual data on breastfeeding initiation (2005-2006 to 2012-2013) and any breastfeeding at 6-8 weeks (2008-2009 to 2012-2013) for 151 primary care trusts (PCTs). Overall, breastfeeding initiation rose from 65.5% in 2005-2006 to 72.4% in 2012-2013 (average annual absolute increase 0.9%). There was a statistically significantly higher (interaction P < 0.001) annual increase in initiation in PCTs in the most deprived (1.2%) compared with the least deprived tertile (0.7%), and in PCTs with low baseline breastfeeding initiation (2005-2006; 1.4%) compared with high baseline initiation (0.6%). Similar trends were observed when PCTs were stratified by the proportion of teenage mothers and maternal smoking, but not when stratified by ethnicity. Although breastfeeding prevalence at 6-8 weeks also increased significantly over the observed time period (41.2% in 2008-2009, 43.7% in 2012-2013; annual increase 0.7%), there was no difference in the average increase by deprivation profile, ethnicity, teenage mothers and maternal smoking. However, PCTs with low baseline prevalence in 2008-2009 saw a significantly larger annual increase (0.8%) compared with PCTs with high baseline prevalence (0.07%). In conclusion, breastfeeding initiation and prevalence have seen higher increases in areas with low initial breastfeeding, and for initiation, more disadvantaged areas. Although these results suggest that inequalities in breastfeeding have narrowed, rates have plateaued since 2010-2011. Sustained efforts are needed to address breastfeeding inequalities.